Synthesis of indole-derived allocolchicine congeners exhibiting pronounced anti-proliferative and apoptosis-inducing properties. Issue 12 (30th October 2015) - Sitnikov, Nikolay S.; Sinzov, Alexander V.; Allegro, Diane; Barbier, Pascale; Combes, Sebastien; Onambele, Liliane Abodo; Prokop, Aram; Schmalz, Hans-Günther; Fedorov, Alexey Yu.
Abstract : The synthesis and biological assessment of indole-based allocolchicine congeners with potent anti-proliferative and apoptosis-inducing activity are reported. Abstract : Based on the natural antimitotic agent allocolchicine as a lead structure, a series of novel indole-based allocolchicine congeners was synthesized and assessed in vitro for their cytostatic properties. Several compounds exhibited potent anti-proliferative and apoptosis-inducing activity towards lymphoma cells along with low unspecific cytotoxicity. The observed activity is supposed to result from the inhibition of microtubule assembly, as indicated by the tubulin polymerisation assay.